IMPLEMENTATION OF DEEP LEARNING BASED PEER TEACHING IN DESCRIPTIVE TEXT WRITING LEARNING FOR STUDENTS OF STATE JUNIOR HIGH SCHOOL - Joko Purwanto; Umi Faizah; Eriana Eriana; Rita Ferina; Dia Widyawati Amat (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study examines how well State Junior High School 4 Purworejo pupils’ descriptive writing abilities are improved by peer instruction based on deep learning. While prior research has looked at peer teaching to improve collaborative learning and deep learning to foster higher order thinking, there are still few studies that combine both strategies in the context of descriptive text writing. This gap makes the current study a unique contribution. A quasi experimental non equivalent control group design was combined with a qualitative examination of students’ views in a mixed method methodology. Purposive sampling was used to choose 60 students, who were split evenly between the experimental and control groups. An analytical rubric comprising topic, structure, vocabulary, grammar, and mechanics was used to assess writing skills. Compared to the control group (74.2), the experimental group’s mean posttest score was higher (83.4). The superior efficacy of the suggested model was demonstrated by an independent t-test, which yielded a significant value of 0.003 (p< 0.05). Students in the experimental group reported more knowledge (87%), greater writing confidence (81%), and higher motivation (90%), according to qualitative results from surveys and interviews. These findings demonstrate that incorporating deep learning concepts knowledge construction, reflective inquiry, and meaningful collaboration into peer instruction provides a pedagogically sound and theoretically sound strategy for enhancing descriptive writing abilities.